In silico analysis, structural modelling and molecular docking of putative Klebsiella pneumoniae choline kinase - Albaskeni, Abdulrhman Mahmoud (2021)
The frightening development of antimicrobial resistant bacteria (AMR) poses an explicit threat to life. This threat is still in an upward curve due to the indiscriminate and overuse of antimicrobials. Therefore, it is essential for the scientific community to keep pace with this development and search for alternative solutions to stop AMR. Choline kinase (ChoK) is considered as one of the new targets for inhibition to combat AMR. In Gram-positive bacteria, choline kinase is responsible for the synthesis of phosphorylcholine, a precursor of lipoteichoic acid and cell wall teichoic acid. In Gram-negative bacteria, phosphorylcholine is incorporated into the membrane lipopolysaccharides. Human choline kinase inhibitor (ChoKIs) has already been tested on Streptococcus pneumoniae with encouraging results by causing degradation of bacterial cell wall. In this study, in silico bioinformatics analysis of putative Klebsiella pneumoniae choline kinase (KpChoK) was performed to search for the best conditions for the production of recombinant KpChoK in the future. Evaluation of ChoKIs as the potential inhibitors of KpChoK by structural modeling and molecular docking approaches were also carried out. The prediction of protein solubility revealed that the solubility of KpChoK was lower than that of the average soluble Escherichia coli proteins. Molecular docking of KpChoK model structures with hemicholinium-3 (HC-3), a well-established ChoKI, showed a suitable binding mode within the choline binding pocket, indicating a promising competitive inhibition by HC-3. These results of molecular docking thus indicate the promising application of ChoKIs to combat antimicrobial resistance. Therefore, this study paved the way towards successful overexpression of soluble KpChoK to be tested with currently available ChoKIs and reveals the potential of these compounds as novel anti-K. pneumoniae agents. Although the KpChoK was predicted to have low solubility in E. coli expression system, several methods have been discussed to improve the solubility. In the future, nanoparticles can also be used to enhance the activity of ChoKIs by acting as a drug delivery system.